2001
DOI: 10.3168/jds.s0022-0302(01)70164-6
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Poly(ethylene terephthalate) and High-Density Polyethylene in Protection of Milk Flavor

Abstract: The development of certain off-flavors in whole milk (3.25% milk fat) as related to packaging material [glass, high-density polyethylene (HDPE), amber poly(ethylene terephthalate) (PETE), clear PETE, and clear PETE-UV] were evaluated after exposure to fluorescent light (1100 to 1300 lx) for 18 d at 4 degrees C. Control samples packaged and stored under identical conditions were wrapped in foil to prevent light exposure. Selected flavor compounds in milk were measured analytically on d 0, 7, 14, and 18 of stora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 10 publications
5
35
0
1
Order By: Relevance
“…Current sensory results are in agreement with those of Van Aardt et al (2001) who reported better milk keeping quality in amber PET and UV compounded PET vs. clear PET bottles as well as those of Cladman et al (1998) who reported superior milk protection against light oxidation when packaged in green PET vs. clear PET bottles. What should be stressed at this point is that even though the total microbial count was in all cases below the ''so called'' upper limit for acceptability 10 6 -10 7 cfu mL À1 the organoleptic characters of the product had clearly deteriorated resulting in an unacceptance product.…”
Section: Sensory Evaluationsupporting
confidence: 89%
See 2 more Smart Citations
“…Current sensory results are in agreement with those of Van Aardt et al (2001) who reported better milk keeping quality in amber PET and UV compounded PET vs. clear PET bottles as well as those of Cladman et al (1998) who reported superior milk protection against light oxidation when packaged in green PET vs. clear PET bottles. What should be stressed at this point is that even though the total microbial count was in all cases below the ''so called'' upper limit for acceptability 10 6 -10 7 cfu mL À1 the organoleptic characters of the product had clearly deteriorated resulting in an unacceptance product.…”
Section: Sensory Evaluationsupporting
confidence: 89%
“…Spectral transmission characteristics over the wavelength range of 350-780 nm (Rysstad et al, 1998;Van Aardt et al, 2001) for all packaging materials were measured with a Shimadzu, model 2100 UV-VIS recording spectrophotometer.…”
Section: Light Transmission Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…A panel of 17 individuals consisting of faculty and graduate students of the Department of Chemistry were trained, in two sessions, for a period of three weeks to differentiate between various off-flavours in milk samples by preparing and evaluating common off-flavour reference standards (light oxidized, plastic acetaldehyde and lack of freshness) (Van Aardt, Duncan, Marcy, Long, & Hackney, 2001). Sensory data were collected between days 0 and 8 of storage.…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…It is also possible that the migration of certain organic UV absorbers contained in UV-blocking films affects food safety (Pascall et al, 1995). For these reasons, the development of a safe and transparent UV-blocking film is currently required in the food industry (Fanelli et al, 1985;Irissin-Mangata et al, 2000;Schroder et al, 1985;Van Aardt et al, 2001).…”
Section: Introductionmentioning
confidence: 99%